An important role for adenine, cholera toxin, hydrocortisone and triiodothyronine in the proliferation, self-renewal and differentiation of limbal stem cells in vitro. (November 2016) - Yu, Min; Bojic, Sanja; Figueiredo, Gustavo S.; Rooney, Paul; de Havilland, Julian; Dickinson, Anne; Figueiredo, Francisco C.; Lako, Majlinda
Abstract: The cornea is a self-renewing tissue located at the front of the eye. Its transparency is essential for allowing light to focus onto the retina for visual perception. The continuous renewal of corneal epithelium is supported by limbal stem cells (LSCs) which are located in the border region between conjunctiva and cornea known as the limbus. Ex vivo expansion of LSCs has been successfully applied in the last two decades to treat patients with limbal stem cell deficiency (LSCD). Various methods have been used for their expansion, yet the most widely used culture media contains a number of ingredients derived from animal sources which may compromise the safety profile of human LSC transplantation. In this study we sought to understand the role of these components namely adenine, cholera toxin, hydrocortisone and triiodothyronine with the aim of re-defining a safe and GMP compatible minimal media for the ex vivo expansion of LSCs on human amniotic membrane. Our data suggest that all four components play a critical role in maintaining LSC proliferation and promoting LSC self-renewal. However removal of adenine and triiodothyronine had a more profound impact and led to LSC differentiation and loss of viability respectively, suggesting their essential role for ex vivo expansion of LSCs. Replacement of each of the components with GMP-grade reagents resulted in equal growth to non-GMP grade media, however an enhanced differentiation of LSCs was observed, suggesting that additional combinations of GMP grade reagents need to be tested to achieve similar or better level of LSC maintenance in the same manner as the traditional LSC media. Highlights: Adenine, cholera toxin, hydrocortisone and triiodothyronine are essential for LSCs proliferation and self-renewal. Adenine and triiodothyronine had a more profound impact as their removal led to LSC differentiation and loss of viability. Removal of each of four components from traditional culture media may pose a risk for clinical translations. New media composition in compliance with Good Manufacturing Practice is proposed.